Novel RP-HPLC method for quantification of peramivir and its impurity (1H-1,2,4-triazole-1-carboximidamide) in bulk and injectable preparations - Anitha Nandagopal; Nemala Appala Raju (Discover Chemistry)
Abstract This study presents a novel and robust reversed-phase high-performance liquid chromatography (RP-HPLC) method for the quantification of peramivir and its process-related impurity, 1H-1,2,4-triazole-1-carboximidamide, in bulk drug substances and injectable formulations. Chromatographic separation was achieved using an Agilent Eclipse-XDB C18 column and a mobile phase consisting of potassium dihydrogen phosphate buffer (pH 3.2) and acetonitrile in a 50:50 (v/v) ratio, at a flow rate of 1.0 mL/min. Detection was performed using a photodiode array (PDA) detector at 260 nm. The method was validated according to ICH Q2(R2) guidelines for specificity, linearity, limits of detection (LOD) and quantification (LOQ), system suitability, precision, accuracy, robustness, and stability. Results demonstrated that the method is precise, reproducible, and reliable for simultaneous estimation of peramivir and its impurity, offering significant utility for pharmaceutical quality control and research purposes.